Nickel-iron-manganese precursor, sodium-ion battery positive electrode material, preparation method and application
Patent Information
- Application Number
- CN202611126313.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-16
AI Technical Summary
(1)内核(Ni-Fe-Mn)与外壳(Zn-Mg共掺杂)之间化学成分差异显著、晶格参数不匹配,在烧结过程中形成界面扩散势垒,阻碍钠源充分扩散进入内核,导致内核镍铁锰的钠化程度不足,活性物质利用率偏低;
[0017] The present invention has the following beneficial effects: The nickel-iron-manganese precursor provided by the present invention comprises a core, an intermediate layer, and an outer coating layer. All three layers contain nickel, iron, and manganese. The intermediate layer and the outer coating layer also contain doping elements; the doping element in the intermediate layer is zinc, and the doping elements in the outer coating layer are zinc and magnesium. The sodium-ion battery cathode material prepared from the three-layer gradient core-shell structure precursor provided by the present invention can significantly improve electrochemical performance, with systematic improvements in initial capacity, first-cycle coulombic efficiency, high-rate performance, and long-cycle stability.
Smart Images

Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of sodium-ion battery technology, and more specifically, to nickel-iron-manganese precursors, sodium-ion battery cathode materials, their preparation methods, and applications. Background Technology
[0002] Layered transition metal oxides are an important branch of sodium-ion battery cathode materials, with O3-type NaNi being a key industrial product. 1 / 3Fe 1 / 3 Mn 1 / 3 O2 (NFM111) suffers from severe structural degradation during charge and discharge. Its cycle performance can be improved to some extent through elemental doping (such as Cu, Zn, Mg, Ti, etc.) or surface coating. Among these, Zn... 2+ It can effectively suppress phase transition, Mg 2+ It can stabilize the crystal lattice and enhance surface inertness.
[0003] However, the improvement effect of single doping on materials is limited, such as Zn. 2+ It readily migrates under high voltage and catalyzes electrolyte decomposition; Mg 2+ The bulk phase control capability is also limited. In the prior art, CN118572084A discloses a core-shell sodium electrode material, comprising a nickel-iron-manganese core and a zinc-magnesium co-doped shell, which improves the material's cycle stability, rate performance, and capacity. However, the following problems still exist: (1) The chemical composition of the core (Ni-Fe-Mn) and the shell (Zn-Mg co-doped) are significantly different and the lattice parameters are mismatched. During the sintering process, an interfacial diffusion barrier is formed, which hinders the full diffusion of sodium source into the core, resulting in insufficient sodiumization of nickel-iron-manganese in the core and low utilization of active material. (2) During the electrochemical cycle, Na + It is necessary to repeatedly cross the core-shell abrupt interface, which has a large interface impedance. The charge compensation ability of active elements such as Ni and Fe in the core cannot be fully utilized, resulting in the actual specific capacity being lower than the theoretical specific capacity. Moreover, the capacity decay intensifies with the increase of the number of cycles. (3) The fixed ratio of Zn and Mg in the outer shell layer cannot spatially decouple and gradient optimize the phase transition suppression function of Zn and the surface stabilization function of Mg, which limits the further improvement of cycle stability and rate performance.
[0004] Therefore, there is an urgent need to optimize layered transition metal oxides to improve the rate performance and cycle stability of batteries.
[0005] In view of this, the present invention is proposed. Summary of the Invention
[0006] The purpose of this invention is to provide nickel-iron-manganese precursors, sodium-ion battery cathode materials, preparation methods, and applications, aiming to improve the rate performance and cycle stability of batteries.
[0007] This invention is implemented as follows: In a first aspect, the present invention provides a nickel-iron-manganese precursor, comprising a core, an intermediate layer and an outer coating layer, wherein the core, the intermediate layer and the outer coating layer each contain nickel, iron and manganese, and the intermediate layer and the outer coating layer further contain doping elements, wherein the doping element of the intermediate layer is zinc, and the doping elements of the outer coating layer are zinc and magnesium.
[0008] In an optional implementation, zinc accounts for 1.3% to 6.4% of the total metal elements in the intermediate layer. And / or, in the total amount of metallic elements in the outer coating, the molar percentage of zinc is 1.2% to 6.3%, and the molar percentage of magnesium is 1.6% to 6.4%; And / or, in the nickel-iron-manganese precursor, the zinc doping amount accounts for 1.0% to 6.0% of the total molar amount of nickel-iron-manganese-zinc-magnesium; And / or, in the nickel-iron-manganese precursor, the amount of magnesium doping accounts for 0.3% to 3.0% of the total molar amount of nickel-iron-manganese-zinc-magnesium; And / or, in the nickel-iron-manganese precursor, the molar ratio of Ni, Fe, and Mn is (0.30–0.35):(0.30–0.35):(0.30–0.35); And / or, the core particle size is 3μm to 9μm, the thickness of the intermediate layer is 1μm to 2μm, and the thickness of the outer coating layer is 1μm to 2μm; And / or, the particle size D50 of the nickel-iron-manganese precursor is 5 μm to 12 μm; And / or, the tap density of the nickel-iron-manganese precursor is ≥1.3 g / cm³. 3 ; And / or, the specific surface area of the nickel-iron-manganese precursor is 8m². 2 / g~18m 2 / g.
[0009] In a second aspect, the present invention provides a method for preparing the nickel-iron-manganese precursor of any of the foregoing embodiments, comprising: Core precipitation: Nickel-iron-manganese core precursors were obtained by co-precipitation deposition using nickel salts, iron salts and manganese salts; Intermediate layer precipitation: Co-precipitation deposition using nickel salts, iron salts, manganese salts and zinc salts to form an intermediate layer on the nickel-iron-manganese core precursor; External coating deposition: Co-precipitation deposition of nickel salts, iron salts, manganese salts, zinc salts and magnesium salts is used to form an external coating layer on the intermediate layer.
[0010] In an optional embodiment, the step of preparing the nickel-iron-manganese core precursor includes: introducing a mixed salt solution containing nickel-iron-manganese, a precipitant, and a complexing agent into a reaction vessel to carry out the reaction, controlling the reaction temperature at 50℃~60℃, the pH value at 10.0~11.0, the ammonia concentration in the system at 0.5g / L~5.0g / L, and reacting until the particle size reaches 3μm~9μm; Preferably, the total concentration of nickel, iron, and manganese in the mixed salt solution used in preparing the nickel-iron-manganese core precursor is 1.5 mol / L to 2.5 mol / L; Preferably, the precipitant used in preparing the nickel-iron-manganese core precursor is a NaOH solution with a concentration of 1.0 mol / L to 4.0 mol / L; Preferably, the complexing agent used in preparing the nickel-iron-manganese core precursor is an aqueous ammonia solution with a concentration of 5 mol / L to 10 mol / L.
[0011] In an optional embodiment, the step of forming the intermediate layer includes: introducing a mixed salt solution containing nickel, iron, manganese, and zinc, a precipitant, and a complexing agent into a reaction vessel to carry out the reaction, controlling the reaction temperature at 50°C to 60°C, the pH value at 10.0 to 11.0, the ammonia concentration in the system at 3.0 g / L to 8.0 g / L, and reacting until the particle size reaches 4 μm to 11 μm; Preferably, the precipitant used in forming the intermediate layer is a NaOH solution with a concentration of 1.0 mol / L to 4.0 mol / L; Preferably, the complexing agent used in forming the intermediate layer is an aqueous ammonia solution with a concentration of 5.0 mol / L to 10 mol / L.
[0012] In an optional embodiment, the step of forming the outer coating layer includes: introducing a mixed salt solution containing nickel, iron, manganese, zinc, and magnesium, a precipitant, and a complexing agent into a reaction vessel for reaction, controlling the reaction temperature at 50℃~60℃, the pH value at 10.0~11.0, the ammonia concentration in the system at 3.0g / L~8.0g / L, reacting until the particle size reaches 5μm~12μm, and after the reaction is completed, performing solid-liquid separation, and washing and drying the obtained solid material; Preferably, the drying temperature is 80℃~120℃, and the drying time is 8h~24h.
[0013] Thirdly, the present invention provides a method for preparing a sodium-ion battery cathode material, wherein a nickel-iron-manganese precursor prepared by any of the foregoing embodiments or by any of the foregoing methods is sintered with a sodium source.
[0014] In an optional embodiment, the molar ratio of sodium to the total amount of transition metal TM is controlled to be (1.00~1.10):1; Preferably, the nickel-iron-manganese precursor and sodium source are first mixed and ball-milled, then pre-calcined at 300℃~500℃ for 2h~6h, and then calcined at 850℃~950℃ for 10h~20h. Preferably, the ball milling speed is 200 rpm to 400 rpm, and the ball milling time is 2 h to 6 h; Preferably, both pre-firing and calcination are carried out in an air atmosphere.
[0015] Fourthly, the present invention provides a sodium-ion battery cathode material, which is prepared by any of the preparation methods described in the foregoing embodiments.
[0016] Fifthly, the present invention provides a sodium-ion battery, including the sodium-ion battery cathode material of the aforementioned embodiments.
[0017] The present invention has the following beneficial effects: The nickel-iron-manganese precursor provided by the present invention comprises a core, an intermediate layer, and an outer coating layer. All three layers contain nickel, iron, and manganese. The intermediate layer and the outer coating layer also contain doping elements; the doping element in the intermediate layer is zinc, and the doping elements in the outer coating layer are zinc and magnesium. The sodium-ion battery cathode material prepared from the three-layer gradient core-shell structure precursor provided by the present invention can significantly improve electrochemical performance, with systematic improvements in initial capacity, first-cycle coulombic efficiency, high-rate performance, and long-cycle stability. Detailed Implementation
[0018] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0019] This invention provides a nickel-iron-manganese precursor, comprising a core, an intermediate layer, and an outer coating layer. The core, intermediate layer, and outer coating layer all contain nickel, iron, and manganese. The intermediate layer and outer coating layer also contain doping elements: the intermediate layer is doped with zinc, and the outer coating layer is doped with zinc and magnesium. The core does not contain Zn or Mg dopants. The content of other metal elements, except for Na, Ni, Fe, Mn, Zn, and Mg, is less than 300 ppm.
[0020] It should be noted that since all three layers (inner, middle, and outer) contain nickel, iron, and manganese, the variation in element types between each layer is reduced, the lattice difference is decreased, and during sintering, Na... + The reduced interfacial diffusion impedance is beneficial to Na +Diffusion extends to the core, fully utilizing the capacity of nickel-iron alloys. By controlling the types of doping elements in the intermediate and outer coating layers, and decoupling the three functions of "capacity contribution layer - phase transition control layer - surface protection layer" through a three-layer gradient spatial layout, it is beneficial to achieve a comprehensive improvement in electrochemical performance, with systematic improvements in initial capacity, first-cycle coulombic efficiency, high-rate performance, and long-cycle stability.
[0021] In some embodiments, the molar percentage of zinc in the total metal element content of the intermediate layer is 1.3% to 6.4%, such as 1.3%, 2%, 3%, 4%, 5%, 6%, 6.4%, etc. In the total metal element content of the outer coating layer, the molar percentage of zinc is 1.2% to 6.3%, such as 1.2%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.3%, etc. The molar percentage of magnesium is 1.6 mol% to 6.4 mol%, such as 1.6%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.4%, etc. Adjusting the amount of doped elements in the intermediate layer and the outer coating layer is beneficial for further improving electrochemical performance.
[0022] In some embodiments, in the nickel-iron-manganese precursor, the zinc doping amount accounts for 1% to 6.0% of the total molar amount of nickel-iron-manganese-zinc-magnesium, such as 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, etc., where this percentage refers to molar percentage. In the nickel-iron-manganese precursor, the magnesium doping amount accounts for 0.3% to 3.0% of the total molar amount of nickel-iron-manganese-zinc-magnesium, such as 0.30%, 0.50%, 0.80%, 1.00%, 1.50%, 2.00%, 2.50%, 3.00%, etc., where this percentage refers to molar percentage.
[0023] Furthermore, in the nickel-iron-manganese precursor, the molar ratio of Ni, Fe, and Mn is (0.30–0.35):(0.30–0.35):(0.30–0.35), with the three molar ratios being essentially equal. The molar ratios of nickel, iron, and manganese in the core, intermediate layer, and outer coating layer can be the same or slightly different, but can all be controlled within the aforementioned molar ratio range.
[0024] In some embodiments, the core particle size D50 is 3μm to 9μm, such as 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, etc.; the thickness of the intermediate layer is 1μm to 2μm, such as 1.0μm, 1.3μm, 1.5μm, 1.8μm, 2.0μm, etc.; the thickness of the outer coating layer is 1μm to 2μm, such as 1.0μm, 1.3μm, 1.5μm, 1.8μm, 2.0μm, etc. The nickel-iron-manganese precursor particle size D50 is 5μm to 12μm, such as 5μm, 8μm, 10μm, 12μm, etc.
[0025] Furthermore, the nickel-iron-manganese precursor particles are spherical or near-spherical, with a tap density ≥1.3 g / cm³. 3 The specific surface area of the nickel-iron-manganese precursor is 8m². 2 / g~18m 2 / g, such as 8m 2 / g, 10m 2 / g、12m 2 / g、14m 2 / g, 16m 2 / g、18m 2 / g etc.
[0026] This invention provides a method for preparing a nickel-iron-manganese precursor with the aforementioned three-layer structure. The method employs a stepwise sequential co-precipitation method to prepare the three-layer gradient precursor, which differs from traditional one-step co-precipitation or solid-phase mixing methods. The specific steps are as follows: S1, Kernel Deposits Nickel-iron-manganese core precursors with satisfactory particle size were obtained by co-precipitation deposition using nickel salts, iron salts, and manganese salts.
[0027] In some embodiments, the steps for preparing the nickel-iron-manganese core precursor include: mixing nickel salt, iron salt, and manganese salt in a molar ratio (e.g., a molar ratio of 1:1:1) to prepare a mixed salt solution; adding pure water as a base liquid to a reactor equipped with a mechanical stirrer and an automatic pH control system; purging with nitrogen or argon gas for protection; adding the mixed salt solution, precipitant, and complexing agent to the reactor in parallel flow via a metering pump for reaction; controlling the reaction temperature at 50℃~60℃ (e.g., 50℃, 53℃, 55℃, 58℃, 60℃, etc.); maintaining the pH value at 10.0~11.0 (e.g., 10.0, 10.3, 10.5, 10.8, 11.0, etc.); maintaining the ammonia concentration in the system at 0.5g / L~5g / L; maintaining the stability of the reaction system by adjusting the feeding rate; continuing the reaction until the particle size reaches 3μm~9μm; stopping the feeding to obtain a pure Ni-Fe-Mn core precursor.
[0028] In some embodiments, the total concentration of nickel, iron, and manganese in the mixed salt solution used in preparing the nickel-iron-manganese core precursor is 1.5 mol / L to 2.5 mol / L, such as 1.5 mol / L, 1.8 mol / L, 2.0 mol / L, 2.3 mol / L, 2.5 mol / L, etc. The nickel salt can be any soluble nickel salt, such as NiSO4; the iron salt can be FeSO4; and the manganese salt can be MnSO4.
[0029] In some embodiments, the precipitant used in preparing the nickel-iron-manganese core precursor is a NaOH solution with a concentration of 1.0 mol / L to 4.0 mol / L, specifically 1.0 mol / L, 2.0 mol / L, 3.0 mol / L, 4.0 mol / L, etc. The complexing agent used in preparing the nickel-iron-manganese core precursor is an ammonia solution with a concentration of 5.0 mol / L to 10 mol / L, specifically 5.0 mol / L, 7.0 mol / L, 9.0 mol / L, 10.0 mol / L, etc.
[0030] S2, intermediate layer precipitate An intermediate layer is formed on a nickel-iron-manganese core precursor by co-precipitation deposition using nickel salts, iron salts, manganese salts, and zinc salts.
[0031] In some embodiments, after step S1, while keeping the reaction temperature and pH constant, a mixed salt solution containing nickel, iron, manganese, and zinc, a precipitant, and a complexing agent are simultaneously introduced into the reactor to carry out the reaction. The reaction temperature is controlled at 50°C to 60°C (e.g., 50°C, 53°C, 55°C, 58°C, 60°C, etc.), the pH value is 10.0 to 11.0 (e.g., 10.0, 10.3, 10.5, 10.8, 11.0, etc.), the ammonia concentration in the system is 3.0 g / L to 8.0 g / L, and the reaction continues until the particle size reaches 4 μm to 11 μm (at which point the thickness of the intermediate layer is approximately 1 μm to 2 μm). The addition rate of ZnSO4 is controlled according to the target Zn doping amount.
[0032] Further, the precipitant is a NaOH solution with a concentration of 1.0 mol / L to 4.0 mol / L, specifically 1.0 mol / L, 2.0 mol / L, 3.0 mol / L, 4.0 mol / L, etc. The complexing agent is an ammonia solution with a concentration of 5.0 mol / L to 10 mol / L, specifically 5.0 mol / L, 7.0 mol / L, 9.0 mol / L, 10.0 mol / L, etc. The concentration of the complexing agent is increased to 3.0 g / L to 8.0 g / L to enhance the reaction with Zn. 2+ Its complexing ability prevents it from rapidly precipitating and causing segregation.
[0033] S3, outer coating layer deposition Co-precipitation deposition using nickel salts, iron salts, manganese salts, zinc salts, and magnesium salts forms an outer coating layer on the intermediate layer.
[0034] In some embodiments, the step of forming the outer coating layer includes: adding a magnesium salt solution containing nickel, iron, manganese, zinc, and magnesium to the reaction system while keeping the reaction temperature and pH constant, wherein the addition rate of the magnesium salt is controlled according to the target Mg doping amount. Simultaneously, a mixed salt solution containing nickel, iron, manganese, zinc, and magnesium, a precipitant, and a complexing agent are introduced to carry out the reaction, controlling the reaction temperature at 50°C to 60°C, the pH value at 10.0 to 11.0, and the ammonia concentration in the system at 3.0 g / L to 8.0 g / L, reacting until the particle size reaches 5 μm to 12 μm (the outer coating layer thickness is 1 to 2 μm).
[0035] Furthermore, the precipitant used in forming the outer coating layer is a NaOH solution with a concentration of 1.0 mol / L to 4.0 mol / L, specifically at concentrations of 1.0 mol / L, 2.0 mol / L, 3.0 mol / L, 4.0 mol / L, etc. The complexing agent is an ammonia solution with a concentration of 5.0 mol / L to 10 mol / L, specifically at concentrations of 5.0 mol / L, 7.0 mol / L, 9.0 mol / L, 10.0 mol / L, etc.
[0036] Further, after the reaction is complete, solid-liquid separation is performed. The obtained solid material is washed and dried to obtain a precursor with a three-layer gradient structure of Ni-Fe-Mn (core) / Ni-Fe-Mn-Zn (middle layer) / Ni-Fe-Mn-Zn-Mg (outer layer). The solid-liquid separation method is not limited, such as filtration. Washing can be performed multiple times with water until SO4 is removed from the washing liquid. 2- The concentration is below 1000 ppm. The drying temperature is 80℃~120℃, such as 80℃, 90℃, 100℃, 110℃, 120℃, etc.; the drying time is 8h~24h, such as 8h, 10h, 13h, 15h, 18h, 20h, 24h, etc.
[0037] This invention provides a method for preparing a sodium-ion battery cathode material, which involves sintering a nickel-iron-manganese precursor provided in this invention with a sodium source.
[0038] In some embodiments, the molar ratio of sodium to the total amount of transition metal TM is controlled to be (1.00~1.10):1, such as 1.00:1, 1.03:1, 1.05:1, 1.08:1, 1.10:1, etc. The type of sodium source is not limited, such as Na2CO3, NaOH, or NaNO3.
[0039] In some embodiments, the nickel-iron-manganese precursor and sodium source are first uniformly mixed using a planetary ball mill, then pre-calcined at 300℃~500℃ for 2h~6h, followed by calcination at 850℃~950℃ for 10h~20h. After natural cooling to room temperature, the final three-layer gradient high-entropy sodium cathode material is obtained. Specifically, the pre-calcination temperature can be 300℃, 350℃, 400℃, 450℃, 500℃, etc.; the pre-calcination time can be 2h, 3h, 4h, 5h, 6h, etc. The calcination temperature can be 850℃, 880℃, 900℃, 930℃, 950℃, etc.; the calcination time can be 10h, 13h, 15h, 18h, 20h, etc. Both pre-calcination and calcination are carried out in an air atmosphere. The heating rate is not limited, such as 1~5℃ / min.
[0040] Furthermore, during the ball milling process, the ball milling speed is controlled at 200 rpm to 400 rpm, such as 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm, etc.; the ball milling time is 2 hours to 6 hours, such as 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, etc.
[0041] It should be noted that this invention employs a two-stage sintering process. The first sintering fully embeds the sodium source and initially forms a layered structure, while the second sintering promotes further interdiffusion of Zn and Mg within the particles. After the two sintering processes, the interlayer boundaries between the original three-layer precursors become blurred, and the concentration distribution of Zn and Mg evolves from a step distribution after the first sintering to a continuous gradient distribution. The final product is actually a single-phase O3-type layered material with a continuous compositional gradient, rather than a multi-layered core-shell structure in the strict sense.
[0042] This invention also provides a sodium-ion battery cathode material, prepared by the method provided in this invention. It is a three-layer gradient high-entropy O3-type cathode material with the chemical formula NaNi. 1 / 3 Fe 1 / 3 Mn 1 / 3 M1 x M2 O2, where M1 is Zn and M2 is Mg.
[0043] This invention also provides a sodium-ion battery, including the sodium-ion battery cathode material provided in this invention.
[0044] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0045] Example 1 This embodiment provides a sodium-ion battery cathode material, and the preparation steps are as follows: (1) Ingredients NiSO4, FeSO4, and MnSO4 were dissolved in water in a molar ratio of Ni:Fe:Mn = 33.33:33.33:33.34 to prepare a NiFeMn mixed salt solution with a total concentration of 2.0 mol / L.
[0046] NiSO4, FeSO4, MnSO4 and ZnSO4 were dissolved in water in a molar ratio of Ni:Fe:Mn:Zn = 32:32:32:4 to prepare a NiFeMnZn mixed salt solution with a total concentration of 1.5 mol / L.
[0047] NiSO4, FeSO4, MnSO4, ZnSO4 and MgSO4 were dissolved in water in a molar ratio of Ni:Fe:Mn:Zn:Mg = 31:31:31:3.8:3.2 to prepare a NiFeMnZnMg mixed salt solution with a total concentration of 1.0 mol / L.
[0048] Sodium hydroxide was dissolved in water to prepare a 2.0 mol / L sodium hydroxide aqueous solution, which was used as a precipitant.
[0049] Prepare a 9.0 mol / L NH3·H2O solution for use as a complexing agent.
[0050] (2) Kernel sedimentation In a reactor equipped with mechanical stirring and an automatic pH control system, pure water was added as the base liquid, nitrogen gas was introduced for protection, the reaction temperature was maintained at 55℃, the pH was controlled at 10.5, and the ammonia concentration was 3 g / L. A Ni-Fe-Mn mixed salt solution, a precipitant, and a complexing agent (0.5 mol / L NH3·H2O solution) were then introduced into the reactor via a metering pump in parallel flow. The reaction system was kept stable by adjusting the feeding rate, and the reaction continued until the particle size reached 5 μm. Feeding was then stopped, yielding a pure Ni-Fe-Mn core precursor.
[0051] (3) Intermediate layer precipitation The NiFeMn mixed salt solution was switched to a 1.5 mol / L NiFeMnZn mixed salt solution, the reaction temperature was maintained at 55℃, the pH was controlled at 10.5, the ammonia concentration was 5 g / L, and the particle size grew to 7 μm.
[0052] (4) Deposition of the outer coating layer The NiFeMnZn mixed salt solution was switched to a NiFeMnZnMg mixed salt solution with a concentration of 1.0 mol / L. The reaction temperature was maintained at 55℃, the pH was controlled at 10.5, the ammonia concentration was 5 g / L, and the particle size was increased to 8.5 μm before the feed was stopped.
[0053] (5) Post-processing After the reaction is complete, the precursor slurry is filtered and washed until SO4 is removed from the washing liquid. 2- The concentration was below 1000 ppm, and then vacuum dried at 100 °C for 20 hours to obtain a precursor with a three-layer gradient structure of Ni-Fe-Mn (core) / Ni-Fe-Mn-Zn (intermediate layer) / Ni-Fe-Mn-Zn-Mg (outer layer).
[0054] (6) Sintering The precursor and Na₂CO₃ were mixed at a molar ratio of Na:TM = 1.05:1, and then mixed uniformly using a planetary ball mill at 300 rpm for 4 hours. The mixed powder was heated to 500°C at 2°C / min in air and held at that temperature for 6 hours. The temperature was then further increased to 900°C at 2°C / min and held for 15 hours. The mixture was then cooled to room temperature in the furnace to obtain the sodium-ion battery layered oxide cathode material (NaNi). 0.32 Fe 0.32 Mn 0.32 Zn 0.03 Mg 0.01 O2), and the content of other metal ion impurities is less than 200 ppm.
[0055] Example 2 The difference from Example 1 is that only the proportions of the three metal elements are changed. Specifically: Core element ratio: NiFeMn (33.33:33.33:33.34); The ratio of elements in the middle layer is: NiFeMnZn (32.9:32.9:32.9:1.3). Outer layer element ratio: NiFeMnZnMg (32.4:32.4:32.4:1.2:1.6); Product: Cathode material (NaNi) 0.328 Fe 0.328 Mn 0.328 Zn 0.01 Mg 0.006 O2) Example 3 The difference from Example 1 is that only the proportions of the three metal elements are changed. Specifically: Core element ratio: NiFeMn (33.33:33.33:33.34); The ratio of elements in the middle layer is: NiFeMnZn (31.2:31.2:31.2:6.4). Outer layer element ratio: NiFeMnZnMg (29.1:29.1:29.1:6.3:6.4); Product: Cathode material (NaNi) 0.31 Fe 0.31Mn 0.31 Zn 0.05 Mg 0.02 O2) Example 4 The difference from Example 1 is that a two-stage sintering process is used: the first sintering is at 450℃ for 8 hours, and the second sintering is at 880℃ for 18 hours.
[0056] Example 5 The difference from Example 1 is that: the first pre-firing is not performed, and the precursor is directly mixed with Na2CO3 and sintered at 900°C for 15 hours.
[0057] Example 6 The only difference from Example 1 is that the particle size after growth in steps (2) to (4) is different: the core particle size is 3 μm; the particle size after deposition of the middle layer is 4 μm; and the particle size after deposition of the outer layer is 5 μm.
[0058] Example 7 The only difference from Example 1 is that the particle size after growth in steps (2) to (4) is different: the core particle size is 9 μm; the particle size after deposition of the middle layer is 11 μm; and the particle size after deposition of the outer layer is 13 μm.
[0059] Comparative Example 1 The difference from Example 1 is that a two-layer core-shell structure was prepared: core: Ni-Fe-Mn (1:1:1) co-precipitated to a particle size of 5 μm; shell: only Zn and Mg (Zn:Mg=1:1) co-precipitated to a particle size of 7 μm.
[0060] Comparative Example 2 Using the precursor from Comparative Example 1, without the first pre-firing, the precursor was directly mixed with Na2CO3 and sintered at 900℃ for 15h.
[0061] Comparative Example 3 The difference from Example 1 is that a uniform doped precursor with a particle size of 8.5 μm was prepared by one-step co-precipitation of Ni, Fe, Mn, Zn, and Mg in a molar ratio of Ni:Fe:Mn:Zn:Mg = 32:32:32:3:1. The same two-stage sintering process as in Example 1 was used.
[0062] Comparative Example 4 The difference from Example 1 is that a two-layer core-shell structure was prepared: Core: Ni-Fe-Mn (1:1:1) co-precipitated to a particle size of 5 μm; Shell: Ni-Fe-Mn-Zn-Mg (32:32:32:3:1) co-precipitated to a particle size of 8.5 μm.
[0063] The performance of the cathode materials prepared in the test examples and comparative examples is shown in Table 1.
[0064] Table 1. Test results of key performance indicators for the cathode materials of the examples and comparative examples.
[0065] The coin cell assembly adopts the CR2032 coin cell configuration. The positive electrode sheet was prepared by weighing the active material:Super P:PVDF at a mass ratio of 8:1:1, using N-methylpyrrolidone as a solvent to form a slurry. After thorough stirring and uniform dispersion, it was coated onto an aluminum foil current collector and dried in a vacuum oven at 120℃ for 12 hours to remove residual solvent and moisture. After drying, the electrode sheet was cut into 12 mm diameter discs using a die-cutting machine and transferred to a glove box filled with high-purity argon (H2O < 0.1 ppm, O2 < 0.1 ppm). The counter electrode was a sodium metal sheet, the separator was a Whatman GF / D glass fiber membrane, and the electrolyte was 1 M NaPF6 dissolved in ethylene carbonate / diethyl carbonate (volume ratio 1:1) with the addition of 2% fluoroethylene carbonate. After assembly, the cells were allowed to stand for 12 hours for aging before testing to ensure sufficient wetting of the electrode materials by the electrolyte.
[0066] Electrochemical performance testing was performed on either the Newway or Blue Ocean multi-channel battery testing system, with the voltage window set at 2.0-4.0 V (vs. Na). + / Na). The first cycle uses a small current of 0.05C for formation treatment to promote the formation of a stable and dense solid electrolyte interphase (SEI) film on the electrode surface, while simultaneously completing the electrochemical activation of the material structure. Subsequently, the initial capacity is tested at 0.1C, the rate performance at 1C, and the capacity reversibility is examined by backtesting at 0.1C. Long-term cycling stability is achieved through 500 continuous cycles at 1C. AC impedance spectroscopy is performed using a Chenhua electrochemical workstation with a frequency range of 100 kHz to 10 mHz and an amplitude of 5 mV. The resulting spectra are fitted with an equivalent circuit model to obtain charge transfer impedance and SEI film impedance. All tests are conducted in a constant temperature chamber at 25±1℃ to eliminate the influence of ambient temperature fluctuations on the test results. The test results are shown in Table 2.
[0067] Table 2 Electrochemical performance test results of the examples and comparative examples
[0068] Analysis of the specific capacity during the first charge cycle: Example 1 achieved 160 mAh / g, an increase of approximately 20 mAh / g compared to Comparative Example 1 (GEM two-layer core-shell structure, 140 mAh / g). This is attributed to the fact that each layer in the three-layer gradient structure contains nickel, iron, and manganese as the main components, and the continuous matching of interlayer lattice parameters allows Na... +There is no interfacial diffusion barrier during sintering and electrochemical deintercalation, enabling full sodiumization and complete electrochemical activity of nickel-iron-manganese in the core region; in Comparative Example 1, the abrupt change in Zn / Mg doping concentration between the core and shell leads to a step in lattice parameters, Na + When migrating to the interface, it encounters a high diffusion barrier, and the active material deep in the core cannot fully participate in the charge compensation reaction, thus limiting the release of capacity.
[0069] Analysis of discharge specific capacity and first-cycle coulombic efficiency: Example 1 achieved 141 mAh / g and 88%, while Comparative Example 1 achieved 120 mAh / g and 86%, further verifying the three-layer gradient structure in Na + Intrinsic advantages in insertion / extraction kinetics. After 500 cycles, Example 1 retained 86% of its capacity, while Comparative Example 1 retained only 76%. This difference is attributed to the microcrack propagation induced by accumulated lattice stress at the core-shell interface of the two-layer structure, and the continuous dissolution of Zn from the shell layer into the electrolyte. The latter catalyzes electrolyte decomposition and leads to a continuous increase in interfacial impedance. The three-layer gradient structure achieves stepwise buffering of volume change stress through the intermediate transition layer, the pinning effect of the surface Mg effectively inhibits Zn dissolution, and the two sintering processes blur the interlayer boundaries. The final product is actually a single-phase structure with a continuous compositional gradient, fundamentally eliminating the phase interface failure path.
[0070] Quantitative evidence of AC impedance data: Example 1: Rct before cycling was 40-50 Ω·cm 2 After 500 cycles, it only increased to 65 Ω·cm. 2 Comparative Example 1 shows a change from 70-80 Ω·cm before the cycle. 2 Climbing to 100 Ω·cm 2 This confirms the significant effectiveness of gradient interfaces in reducing charge transfer impedance and suppressing interface degradation.
[0071] In summary, the three-layer gradient core-shell structure of this invention, combined with a two-stage sintering process, comprehensively surpasses the two-layer core-shell structure in terms of physicochemical indicators such as packing density and interfacial stability. Correspondingly, its electrochemical performance, including initial capacity, first-cycle coulombic efficiency, high-rate performance, and long-cycle stability, shows a systematic improvement. The performance bottleneck of the two-layer core-shell structure stems from the lattice mismatch and diffusion barrier at the single interface between the core and shell, as well as the structure-surface performance conflict caused by the functional coupling of Zn / Mg in the same shell layer. This contradiction cannot be completely eliminated through process optimization. This invention decouples the three functions of the "capacity contribution layer—phase change regulation layer—surface protection layer" through a three-layer gradient spatial layout, and eliminates the interlayer phase boundaries through two sintering processes, forming a single-phase structure with a continuous compositional gradient. This fundamentally solves the problem of intrinsic interfacial instability, demonstrating a leapfrog performance improvement brought about by structural innovation.
[0072] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A nickel-iron-manganese precursor, characterized in that, It includes a core, an intermediate layer, and an outer coating layer. The core, the intermediate layer, and the outer coating layer all contain nickel, iron, and manganese. The intermediate layer and the outer coating layer also contain doping elements. The doping element in the intermediate layer is zinc, and the doping elements in the outer coating layer are zinc and magnesium.
2. The nickel-iron-manganese precursor according to claim 1, characterized in that, In the total amount of metal elements in the intermediate layer, zinc accounts for 1.3% to 6.4% in molar proportion; And / or, in the total amount of metal elements in the outer coating, the molar percentage of zinc is 1.2% to 6.3%, and the molar percentage of magnesium is 1.6% to 6.4%; And / or, in the nickel-iron-manganese precursor, the zinc doping amount accounts for 1.0% to 6.0% of the total molar amount of nickel-iron-manganese-zinc-magnesium; And / or, in the nickel-iron-manganese precursor, the amount of magnesium doping accounts for 0.3% to 3.0% of the total molar amount of nickel-iron-manganese-zinc-magnesium; And / or, in the nickel-iron-manganese precursor, the molar ratio of Ni, Fe, and Mn is (0.30–0.35):(0.30–0.35):(0.30–0.35); And / or, the particle size of the core is 3μm to 9μm, the thickness of the intermediate layer is 1μm to 2μm, and the thickness of the outer coating layer is 1μm to 2μm; And / or, the particle size D50 of the nickel-iron-manganese precursor is 5 μm to 12 μm; And / or, the tap density of the nickel-iron-manganese precursor is ≥1.3 g / cm³. 3 ; And / or, the specific surface area of the nickel-iron-manganese precursor is 8m². 2 / g~18m 2 / g.
3. A method for preparing a nickel-iron-manganese precursor according to any one of claims 1-2, characterized in that, include: Core precipitation: Nickel-iron-manganese core precursors were obtained by co-precipitation deposition using nickel salts, iron salts and manganese salts; Intermediate layer precipitation: The intermediate layer is formed on the nickel-iron-manganese core precursor by co-precipitation deposition using nickel salt, iron salt, manganese salt and zinc salt; Outer coating deposition: The outer coating is formed on the intermediate layer by co-precipitation deposition of nickel salt, iron salt, manganese salt, zinc salt and magnesium salt.
4. The preparation method according to claim 3, characterized in that, The steps for preparing the nickel-iron-manganese core precursor include: introducing a mixed salt solution containing nickel-iron-manganese, a precipitant, and a complexing agent into a reaction vessel for reaction, controlling the reaction temperature at 50℃~60℃, the pH value at 10.0~11.0, the ammonia concentration in the system at 0.5g / L~5.0g / L, and reacting until the particle size reaches 3μm~9μm; Preferably, the total concentration of nickel, iron, and manganese in the mixed salt solution used in preparing the nickel-iron-manganese core precursor is 1.5 mol / L to 2.5 mol / L; Preferably, the precipitant used in preparing the nickel-iron-manganese core precursor is a NaOH solution with a concentration of 1.0 mol / L to 4.0 mol / L; Preferably, the complexing agent used in preparing the nickel-iron-manganese core precursor is an aqueous ammonia solution with a concentration of 5.0 mol / L to 10 mol / L.
5. The preparation method according to claim 3, characterized in that, The steps for forming the intermediate layer include: introducing a mixed salt solution containing nickel, iron, manganese, and zinc, a precipitant, and a complexing agent into a reaction vessel for reaction, controlling the reaction temperature at 50℃~60℃, the pH value at 10.0~11.0, the ammonia concentration in the system at 3.0g / L~8.0g / L, and reacting until the particle size reaches 4μm~11μm; Preferably, the precipitant used in forming the intermediate layer is a NaOH solution with a concentration of 1.0 mol / L to 4.0 mol / L; Preferably, the complexing agent used in forming the intermediate layer is an aqueous ammonia solution with a concentration of 5.0 mol / L to 10 mol / L.
6. The preparation method according to claim 3, characterized in that, The steps for forming the outer coating layer include: introducing a mixed salt solution containing nickel, iron, manganese, zinc, and magnesium, a precipitant, and a complexing agent into a reaction vessel for reaction, controlling the reaction temperature at 50℃~60℃, the pH value at 10.0~11.0, the ammonia concentration in the system at 3.0g / L~8.0g / L, reacting until the particle size reaches 5μm~12μm, and after the reaction is completed, performing solid-liquid separation, and washing and drying the obtained solid material; Preferably, the drying temperature is 80℃~120℃, and the drying time is 8h~24h.
7. A method for preparing a sodium-ion battery cathode material, characterized in that, The nickel-iron-manganese precursor prepared by any one of claims 1-2 or by any one of the preparation methods in claims 3-6 is sintered with a sodium source.
8. The preparation method according to claim 7, characterized in that, The molar ratio of sodium to the total amount of transition metals TM is controlled at (1.00~1.10):1; Preferably, the nickel-iron-manganese precursor and the sodium source are first mixed and ball-milled, then pre-calcined at 300℃~500℃ for 2h~6h, and then calcined at 850℃~950℃ for 10h~20h. Preferably, the ball milling speed is 200 rpm to 400 rpm, and the ball milling time is 2 h to 6 h; Preferably, both pre-firing and calcination are carried out in an air atmosphere.
9. A sodium-ion battery cathode material, characterized in that, It is prepared by the preparation method according to any one of claims 7-8.
10. A sodium-ion battery, characterized in that, Including the sodium-ion battery cathode material as described in claim 9.